Effect of Ti: Sapphire and Nd: YAG Lasers on Shear Bond Strength at the Zirconia - Veneering Ceramic Juncture: Nanosecond and Femtosecond Lasers Impact on the Zirconia – Veneering Ceramic Bond - Abraham, Anamika; Jain, Deshraj; Gupta, Alka; Chakera, J A (Journal of Lasers in Medical Sciences, 2021)
Introduction: This study was conducted to assess the impact of nanosecond and femtosecond lasers on shear bond strength at the zirconia-veneering ceramic juncture. Materials and Methods: The first 60 samples of partially sintered zirconia cylindrical discs measuring 7 mm diameter and 4 mm height were milled and sintered. Then they were randomly divided into three groups namely group C (control, n=10), group N (Nd: YAG laser, n=10), and group T (Ti: sapphire laser n=40) which was further divided based on the duration of laser irradiation, into 4 subgroups (n=10 each) which were 30 seconds, 1 minute, 2 minutes and 3 minutes. Surface treatment was done on sintered zirconia discs based on the group. Following the treatment, the discs were ultrasonically cleaned followed by liner application (IPS Emax Zirliner, Ivoclar-Vivadent) and veneer ceramic layering (IPS e.max Ceram, Ivoclar-Vivadent) of 1.5 mm height. Each sample underwent shear stress in the universal test machine on the mounting jig, and bond strength was evaluated. Data were assessed using ANOVA followed by Tukey’s post hoc multiple comparison analyses. Results: According to one-way ANOVA, there was a significant difference in shear bond strength between the groups. Tukey’s post hoc pairwise comparison test showed a significant difference (P value=0.001) in shear bond strength of all pairs except group C and group N. The results of repeated measures, ANOVA (related and dependent groups), and Tukey’s multiple pairwise comparison test showed that there was a significant difference (P value=0.001) in shear bond strength at 30 seconds and all other groups. Conclusion: Ti: sapphire laser irradiation for 30 seconds can be used as a potential surface treatment to increase shear bond strength at the zirconia-veneering ceramic juncture. DOI: 10.34172/jlms.2021.71.